2015
DOI: 10.1002/pola.27911
|View full text |Cite
|
Sign up to set email alerts
|

Hole‐buffer polymer composed of alternating p‐terphenyl and tetraethylene glycol ether moieties: Synthesis and application in polymer light‐emitting diodes

Abstract: Carrier balance is essential to obtain efficient emission in polymer light-emitting diodes (PLEDs). A new polymer 3P5O composed of alternating p-terphenyl and tetraethylene glycol ether segments is designed and synthesized by the Suzuki coupling reaction and successfully employed as hole-buffer layer to improve carrier balance. Multilayer PLEDs [ITO/ PEDOT:PSS/3P5O/SY/LiF/Al], with Super Yellow (SY) as the emitting layer and 3P5O as the hole-buffer layer, reveal maximum luminance (17,050 cd/m 2 ) and maximum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…p -Terphenyl, an organic scintillation material, is frequently employed as the luminescent material in scintillation counters . Research indicates that p -terphenyl, as a scintillation material, possesses excellent scintillation properties such as high light output, rapid scintillation response, and good energy resolution. This suggests that p -terphenyl can effectively serve as a sensitizer for high-energy radiation, converting it efficiently to photon energy. The photon energy excites the dopants through energy transfer, resulting in distinct luminescent characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…p -Terphenyl, an organic scintillation material, is frequently employed as the luminescent material in scintillation counters . Research indicates that p -terphenyl, as a scintillation material, possesses excellent scintillation properties such as high light output, rapid scintillation response, and good energy resolution. This suggests that p -terphenyl can effectively serve as a sensitizer for high-energy radiation, converting it efficiently to photon energy. The photon energy excites the dopants through energy transfer, resulting in distinct luminescent characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Besides their use in biology and medicine, terphenyl and poly-phenyl compounds have found other important applications, as liquid crystals and fluorescent optoelectronic compounds (18). Functionalized terphenyls, based on di-or tri-amino-1,1 ′ :3 ′ ,1 ′′ -terphenyls, have, for example, been used in charge transporting/ charge generating agents (19,20), metal organic frameworks (21), conducting polymers (22,23), and light emitting diodes (24), whilst the photo-physical properties of o-, m-, and p-terphenyl compounds have been exploited in organic liquid-crystalline materials and organic electroluminescent (OEL) devices by taking advantage of the different organizational arrangements of the aromatic rings in the two dimensional plane (18,25).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, copper (II) phthalocyanine (CuPC), and 4,4',4''-tris (N-carbazolyl)-triphenylamine (TATC) were deposited as hole-buffering layer which effectively reduced hole mobility [14] [15]. We have designed a polymer 3P 5 O composed of alternating p-terphenyl and tetraethylene glycolether segments and successfully employed as hole-bufferlayer to improve carriers balance [16]. The hole buffer layer was inserted between hole injection and emissive layers, it reduces the mobility of holes and thus recombine with electrons in the whole emissive layer, leading to enhanced device performance [16] [17].…”
Section: Introductionmentioning
confidence: 99%
“…We have designed a polymer 3P 5 O composed of alternating p-terphenyl and tetraethylene glycolether segments and successfully employed as hole-bufferlayer to improve carriers balance [16]. The hole buffer layer was inserted between hole injection and emissive layers, it reduces the mobility of holes and thus recombine with electrons in the whole emissive layer, leading to enhanced device performance [16] [17]. In 1999, Forsythe found that transport of holes from ITO anode to NPB hole-transporting layer was injection-limited and device performance depended on hole current [18].…”
Section: Introductionmentioning
confidence: 99%